ASSESSMENT PERILAKU TIDAK AMAN PADA SEKTOR INFORMAL PENGRAJIN BATU AKIK DI PASAR DARGO BARU, SEMARANG - Puspita Panjrah Sumekar; Hanifa Maher Denny; Aditya Kusumawati (Jurnal Kesehatan Masyarakat (Undip), 2017)
Occupational safety and health in the informal sector hasn’t become a concern from the governments, owners or workers. Informal sector of akik stone the sector which contains hazard, can cause accident and disease. Unsafe act can increase the risk. This research method was descriptive qualitative which aims to describe unsafe act of Akik stone’s craftsman at Dargo Baru Market, Semarang and some factors on the act based on L. Green’s theory. Data was collected from observation and indepth interview. The key informants were 6 Akik stone’s craftsmen and informant triangulation consists of 1 coordinator of Paguyuban Pengrajin Batu Akik (P3BA) Dargo Baru Market and 6 craftsman family members. The results showed there were so many unsafe act, such as careless of safety equipment, wearing PPE incorrectly, improper placement, incorrect body posture, frolic, and smoking. Most of those craftsman did know about hazards like machine, dust, electricity and incorrect body posture. Most craftsmen looked at the hazard is a common thing to deal with. Most of them also agreed that their jobs are extremely risky. The craftsmen have sufficient means to behave safely. P3BA not yet provide support in safety program to the craftsmen. Attention of each fellow among of craftsmen about safety is still minimal. Family supports by giving advice to be careful, give advice to drink milk, giving masks and health supplements. Suggestion: P3BA must activate the member so that the duty goes well, should make safety program, and collaborate with Primary Health Care to receive occupational health efforts.